MENYIAPKAN MASA DEPAN DI MASA DINI - Putlia, Grace; Sundoro, Hary Saputra; Wijaya, Brendi; Wardhana, Ali; Rowena, Janny; Budi, Budi; Samuel, Samuel; Pipiyen, Pipiyen (Universitas Bunda Mulia, 2019)
Knowing that human resources are important for the progress of a nation, it is necessary to have early preparation in order to be able to foster the future well. Supported also by the third Tri Dharma of Higher Education - Pengabdian Kepada Masyarakat (PKM), which states that the responsibilities of a teacher include transferring, transforming, and applying knowledge from within the campus to the public. Based on this, the University of Bunda Mulia conducted PKM activities by raising the topic